Spregledani vidiki pokojninske reforme - Strban, Grega (Delavci in delodajalci, 2013)
The legislature was obviously in a hurry when passing the new pension and invalidity insurance act. This is reflected in its structure and content. In the present contribution constitutionally important questions of (un)equal treatment of various economically active groups of persons, access of women and men to an old-age pension, distinctive- and same sex partners to a widow/er's pension and comparable groups of students to a family pension, are being raised. It is doubted whether the act is in full harmony with the EU law and minimum standards of the ILO. Attention is drawn also to the rules of composing a legislative act (nomotechnics), which were not fully observed.
Keywords: invalidsko zavarovanje; pokojnine; pokojninsko zavarovanje; reforma; spremembe